2019
DOI: 10.1007/s13300-019-0619-1
|View full text |Cite
|
Sign up to set email alerts
|

A View Beyond HbA1c: Role of Continuous Glucose Monitoring

Abstract: Hemoglobin A1C (HbA1c) is used as an index of average blood glucose measurement over a period of months and is a mainstay of blood glucose monitoring. This metric is easy to measure and relatively inexpensive to obtain, and it predicts diabetes-related microvascular complications. However, HbA1c provides only an approximate measure of glucose control; it does not address short-term glycemic variability (GV) or hypoglycemic events. Continuous

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
127
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(133 citation statements)
references
References 57 publications
0
127
0
6
Order By: Relevance
“…More recently, an exploratory analysis of DRCR.net Protocol T, in which participants were randomized to receive bevacizumab, ranibizumab, or aflibercept, similarly found the magnitude of vision improvement after anti-VEGF treatment to be associated with HbA1c levels [20]. One possible explanation for the discrepancy between studies is that patients with similar HbA1c levels can have marked differences in their daily glucose profiles, with variable frequency and duration of glucose excursions [22,23]. Transient hyperglycemic spikes can be a HbA1cindependent risk factor for diabetes-related complications, due to transient episodes of oxidative stress [24].…”
Section: Association Of Systemic Factors With Visual Outcome Aftermentioning
confidence: 99%
“…More recently, an exploratory analysis of DRCR.net Protocol T, in which participants were randomized to receive bevacizumab, ranibizumab, or aflibercept, similarly found the magnitude of vision improvement after anti-VEGF treatment to be associated with HbA1c levels [20]. One possible explanation for the discrepancy between studies is that patients with similar HbA1c levels can have marked differences in their daily glucose profiles, with variable frequency and duration of glucose excursions [22,23]. Transient hyperglycemic spikes can be a HbA1cindependent risk factor for diabetes-related complications, due to transient episodes of oxidative stress [24].…”
Section: Association Of Systemic Factors With Visual Outcome Aftermentioning
confidence: 99%
“…However, a persistent glucose-lowering effect over the day is important to ensure sustained improvement of glycaemic control during diabetes therapy. [13][14][15][16] Furthermore, it is also not known whether the difference in pharmacokinetics and enzyme-binding characteristics of the different DPP-4 inhibitors 3 is translated to different effects on glycaemia and islet and incretin hormones over the day. To explore these two questions, we examined the effects of DPP-4 inhibition on glucose and islet and incretin hormones after each meal over a whole day in metformin-treated subjects with T2D, and in this study, we examined three different DPP-4 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between glycemic control and hypertension can be explained by several possible mechanisms. First, function deficits of pancreatic beta cells, as well as insulin resistance could be indicated by the expression, of HbA1c [9,10]. It was well-recognized that insulin resistance was the common pathophysiological basis for the development of both type 2 diabetes and hypertension [28].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance, hyperinsulinemia, and the excitatory effects of hyperglycemia itself may be the underlying mechanisms of hypertension [8]. HbA1c, as a stable indicator of long-term glycemia, can precisely reflect the stability of glycemic control within nearly 8-12 weeks and was also correlated with defects of pancreatic β-cell function, as well as the degree of insulin resistance [9,10]. Other evidence has increasingly demonstrated that not only patients with a higher risk of developing diabetes but also those with cardiovascular diseases could be identified by HbA1c level [11,12].…”
Section: Introductionmentioning
confidence: 99%